Virtual Objects: To Be is to Be Perceivable. - Murphy, Alex (Australasian Journal of Philosophy, 2026)
The objects we interact with in virtual reality—virtual objects—raise metaphysical questions. The most central of these questions is whether virtual objects really exist, that is, whether we ought to be realists about such objects. The most prominent realist metaphysics of virtual objects is David Chalmers' virtual digitalism—the view that virtual objects are digital objects. I propose an alternative realist account—virtual perceptibilism. On this view virtual objects are pure perceptibilia. They are public objects, like rainbows, whose existence and intrinsic nature is dependent on us as perceivers. I contrast perceptibilism with digitalism, showing the superiority of the former. As such, I demonstrate that virtual perceptibilism is the best virtual realism on offer, leaving aside the question of whether perceptibilism is superior to irrealist accounts.